Memória política brasileira da ditadura militar: um estudo histórico, jurídico e filosófico à luz do pensamento de Hannah Arendt - ARAÚJO, Rayssa Marchão (2022)
It approaches the Brazilian political memory of the civil-military dictatorship period (1964- 1985) and aims to carry out a critical reflexive analysis of this historical moment. The research has as main theoretical reference the thought of the contemporary philosopher Hannah Arendt (1906-1975), who was concerned with developing a political-philosophical understanding of the remarkable events of the 20th century. In order to do so, it initially conducts a review regarding the most striking facts of the last century, at a global and national level, especially the totalitarian regimes in Europe in sync with the Estado Novo (1937-1945) in Brazil, for relating them to the episode of the Brazilian military dictatorship. The Amnesty Law of 1979 (Law 6,683) is then presented, with an analysis of its social and legal significance in the political scenario of this period, the issues of responsibility and forgiveness, as well as the imposing characteristic of amnesty by the State, in particular, with respect to the oblivion of crimes against humanity committed by public agents against Brazilian citizens. Finally, the importance of political memory for the current democratic society is emphasized, it is defended as an essential political act that must occur within the public space for reducing the culture of silence regarding the dictatorship, this practice is revealed as a contribution to not forget the state of exception terrors and a prevention of its repetition. It shows that political amnesty can never be used as a maneuver for oblivion to prevail and for collective memory to be despised. It is argued that political memory belongs to the human relations world and must be understood as a phenomenon that is linked to a nation identity and, consequently, is a source of understanding for what we were, we are, and we will be, therefore, the memory is a matter of public character.